Revision of Neotropical Scelolabes Philippi (Diptera, Hybotidae, Ocydromiinae): two new species and a proposal of delimitation - Barros, Luana Machado; Freitas-Silva, Rafael Augusto Pinheiro; Ale-Rocha, Rosaly (European Journal of Taxonomy, 2023)
Scelolabes, historically is a monotypic genus of Ocydromiinae (Hybotidae) that for a long time was not studied due to the absence of the type of the type species (Scelolabes bivittatus Philippi), which is probably lost or destroyed. In this context, we propose an updated diagnosis and redescription of the genus, based on specimens identified by experts and in agreement with the original description of Philippi (1865), as well as illustrating male and female terminalia for the first time. This serves as an aid to discuss and corroborate the status of Scelolabes in the Neotropical region as a genus distinct from Hoplopeza. In addition, two new species are described, and an identification key and a distribution map are provided to all the Neotropical species of the genus.